DEMAND ANALYSIS OF THE OSING COMMUNITY FOR FIRST LEVEL HEALTH FACILITY SERVICE AT THE NATIONAL HEALTH INSURANCE PROGRAM (Proceedings of the International Conference on Public Health, 2017)
The outpatient and hospitalizations visits was low in Banyuwangi, Indonesia indicate that community demand to health services still low. The purpose of this study was to analyze the osing community demand for fisrt level health facility (FLHF) services at the National Health Insurance Program. Type of this research was analytic using cross sectional approach. The population in this study was the family in Kemiren and Olehsari village, Banyuwangi, Indonesia many as 2,026 households. The sample in this study as much as 60 households (300 family members). Multivariate data analysis using multiple logistic regression test. The results showed that there were two factors that affect demand for health service was a education level and knowledge factor (α
Keywords: Demand analysis, Health Services, First Level Health Facility, National Health Insurance